Odpowiedź :
a) 3 x + y = - 5 /razy -2
-6x-2y=10
b)- x + 4 y = 2/razy -1/2
1/2x-2y=-1
c)x - 1/2 y = 1/razy 4
4x-2y=4
d)3 x - 3 y = 1/razy 2/3
2x-2y=2/3
e)x + 3/4 y = 0 /razy - 2 i 2/3
-2 i 2/3-2y=0
-6x-2y=10
b)- x + 4 y = 2/razy -1/2
1/2x-2y=-1
c)x - 1/2 y = 1/razy 4
4x-2y=4
d)3 x - 3 y = 1/razy 2/3
2x-2y=2/3
e)x + 3/4 y = 0 /razy - 2 i 2/3
-2 i 2/3-2y=0
a)
3 x + y = - 5/* (-2)
-6x - 2y = 5
b)
- x + 4 y = 2/* (-1/2)
1/2 - 2y = -1
c)
x - 1/2 y = 1/* 4
4 - 2y =4
d)
3 x - 3 y = 1/* 2/3
2x - 2y = 2/3
e)
x + 3/4 y = 0/* (-2 2/3)
2 2/3 -2y = 0
3 x + y = - 5/* (-2)
-6x - 2y = 5
b)
- x + 4 y = 2/* (-1/2)
1/2 - 2y = -1
c)
x - 1/2 y = 1/* 4
4 - 2y =4
d)
3 x - 3 y = 1/* 2/3
2x - 2y = 2/3
e)
x + 3/4 y = 0/* (-2 2/3)
2 2/3 -2y = 0